Design and Development of Integrated Stationary Cycling Charger for Promoting Healthy Lifestyle - Rasin, Zulhani; Daud, Faiz; Md Zan, Muhammad Amruha; Abd Rani, Natrah; Md Yazid, Mohd Akhmal Syafi (Blue Eyes Intelligence Engineering & Sciences Publication Pvt. Ltd., 2019)
A powerful smartphone with all the high-end features has becomes one of the basic necessitie in today’s modern life. People use the smartphone not only for communication purpose, but for other things such as entertainment, education, and work. As our life has becomes very much dependent on this kind of technological gadget which makes everything easier and faster to access, it becomes a main reason for our lack of daily physical activities which poses potential health issues such as obesity, high cholesterol level and high blood pressure. Despite various brands and models of a smartphone, one thing in common is the use of battery to power the device, where it needs to be recharged over time. The movement of wheel with a motor installed able to generate electricity thus powering the battery. In this research, the enjoyable and healthy activity of cycling is further upgraded to become what is known as a “cycling charger” as a way of promoting a healthy lifestyle within the community. It focuses on the conceptual design and prototype development of a stationary cycling charger which can be located everywhere within the public area for easy access and usability. The specification and parameters of the cycling charger are determined based on the average potential users, including the electrical capacity and device protection. It is then followed by the modelling and simulation works using a software to determine the feasibility before proceeding to the prototyping stage where all the designed circuitries are fabricated and integrated with sensors and microcontrollers for processing information and providing user interface. Lastly, several measurement and operation verification are conducted to ensure a satisfactory operation of the developed cycling charger. It is verified the developed prototype can be operated at a minimum cycling speed a low as 8 km/h which is good for wide range of user with different cycling ability. Its size which is basically based on the available stationary cycling exercise platform and together with an independent battery supply for all its operation make it easier and flexible to be installed within the public area.